On the semi-scalar equivalence of polynomial matrices over a field - Prokip, Volodymyr M. (Modeling, Control and Information Technologies: Proceedings of International scientific and practical conference, 2021)
Polynomial matrices and of size over a field are semi-scalar equivalent if there exist a nonsingular matrix over and an invertible matrix over such that . The aim of the present report is to present a triangular form of some nonsingular polynomial matrices with respect to semi-scalar equivalence.